The Role of Waqf as an Instrument of Islamic Philanthropy in Financing Islamic Education - Bundo, Mayang; Sakinah, Gina; Suratman, Junizar (Jurnal Iqtisaduna, 2025)
Islamic education plays a vital role in shaping individual character and driving the progress of a nation. Islamic philanthropy holds significant potential in supporting the financing of education. Waqf, as one of the philanthropic instruments in Islam, can serve as a sustainable funding source for Islamic educational institutions. This article aims to discuss the role and contributions of Islamic philanthropy, particularly waqf, in the development of Islamic education. The method employed in this study is a literature review, gathering information and data from various relevant sources. The findings of this literature study demonstrate that waqf plays a highly strategic role in financing Islamic education. Waqf can provide a sustainable funding source, improve the quality of educational services, and offer broader access to education for the community. Using waqf can encompass infrastructure development, scholarship provision, curriculum enhancement, and improving educators' welfare.